Sistem Informasi Apotek Happy Berbasis Web - Fiilma Ihzani, Gheasani; Fujiyanti, Linda; Afriansyah, Riki (Jurnal Inovasi Teknologi Terapan, 2024)
Happy pharmacy is a pharmacy that sells medicine located at street Kp. Asam, Kec. Rangkui, Pangkalpinang City, Bangka Belitung Island 33684. In running its business, Happy Pharmacy still uses a conventional system where all information regarding drug sales and sales reports is still done manually. This causes problems such as the problems that occr at the Happy Pangkalpinang Pharmacy, the author created a web-based pharmacy information system with the aim of making it easier for users to process and provide information regarding pharmacy data and to support the work effectiveness and accuracy of existing pharmacy data. the method that the author useus in building a web-based pharmacy information system uses the waterfall method which consists of several stages such as analysis, design, coding, testing and implementation. Data collection techniques used in the web-based pharmacy information system are interviews, observation and literature study. For system development, the language used PHP,MySQL.